Factors Affecting Antenatal Care Visits During the Covid-19 Pandemic in the Working Area of Kantewuka Public Health Center, Sigi Regency Central Sulawesi - Herniyanti; Kasmawati; Ismawati; Zulhaedah (Institute of Computer Science (IOCS), 2022)
Antenatal care is a service provided to pregnant women by carrying out prenatal checks and supervision to optimize the mental and physical health of pregnant women. In this COVID-19 pandemic, many restrictions on almost all routine services, including maternal and neonatal health services. The study aimed to determine the factors influencing antenatal care visits during the COVID-19 pandemic in the working area of Kantewu Health Center, Sigi District. The research used was a Cross-Sectional Study. The sample in this study were all pregnant women who made antenatal care visits, as many as 65 pregnant women using the total sampling technique. The study shows that maternal anxiety is a factor influencing antenatal care visits during the COVID-19 pandemic (p-value = 0.024 < α 0,05), The pandemic period was a factor affecting antenatal care visits during the COVID-19 pandemic (p-value = 0.033 < α 0,05), the attitude was a factor influencing antenatal care visits during the COVID-19 pandemic (p-value = 0.008 < α 0,05), education was a factor influencing antenatal care visits during the COVID-19 pandemic (p-value = 0,016 < α 0,05), mileage was a factor influencing antenatal care visits during the COVID-19 pandemic (p-value = 0.009 <α 0,05). Conclusion: Mother's anxiety, pandemic period, attitude, education, and distance influence antenatal care visits during the COVID-19 pandemic. Suggestion: It is better if health workers need to conduct counseling for pregnant women related to COVID-19 and prevention efforts so that pregnant women are not worried about doing antenatal care during the COVID-19 pandemic.